Queen of Equestria: a study of the career of Lauren Faust and her impact on contemporary animation - Tselentis, Kleanthi (My University, 2021)
The intention of this research is to use the case study method to look at Lauren Faust’s career in the Western animation industry and her impact on contemporary animation with specific look at her female characters. The aim of this research is to understand how Faust is able to create female characters that are relatable and entertaining without removing any aspect innately‘ female’. The character analysis, which will follow the case study, will be isolating two characters of the show My Little Pony: Friendship is Magic that I have found to be the best candidates for an in-depth research into female identity. The character Rarity will be in reference to herself-awareness as a female character with the use of her comedy and the female gaze. The second character, Pinkie Pie, is the self-awareness of being a cartoon while still appealing to the young girl ‘feminine aesthetic’. The analysis also focuses on how Faust’s use of personality animation alongside the medium of cut-out animation is deemed preferrable for exploring ways to delve into the female identity outside of using a gendered body. As a way to understand the differences between tropes and stereotypes, I will also be offering a short analysis on the character Zecora and how her characterisation threatens what has made the show a success. The theoretical discourse coupled with the case study on Faust and analysis on her characters has furthered my own knowledge on developing successful female characters in animation
A dissertation submitted in partial fulfilment of the requirements for the degree of Masters of Arts (Digital Arts) in the Faculty of Humanities, University of the Witwatersrand, 2021